2015
DOI: 10.1596/1813-9450-7338
|View full text |Cite
|
Sign up to set email alerts
|

What Drives Local Food Prices? Evidence from the Tanzanian Maize Market

Abstract: We quantify the relationship between Tanzanian and external maize markets while also accounting for domestic influences. We conclude that external influences on domestic prices originate from regional, rather than global, markets. We also show that, compared to external factors, domestic factors exert a greater influence on Tanzanian maize markets. Further, the mechanisms through which trade policies influence maize markets involve interactions with both external market shocks and domestic weather shocks. Over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(61 citation statements)
references
References 0 publications
3
58
0
Order By: Relevance
“…Regional effects of export controls have been investigated by Baylis et al (2014), Baffes et al (2015) and Ihle et al (2009) following a regime-switching price transmission approach. 2 Baylis et al (2014) and Baffes et al (2015) adopt an approach in which the regime switches are determined exogenously by the knowledge of the time periods when exports were restricted.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Regional effects of export controls have been investigated by Baylis et al (2014), Baffes et al (2015) and Ihle et al (2009) following a regime-switching price transmission approach. 2 Baylis et al (2014) and Baffes et al (2015) adopt an approach in which the regime switches are determined exogenously by the knowledge of the time periods when exports were restricted.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Regional effects of export controls have been investigated by Baylis et al (2014), Baffes et al (2015) and Ihle et al (2009) following a regime-switching price transmission approach. 2 Baylis et al (2014) and Baffes et al (2015) adopt an approach in which the regime switches are determined exogenously by the knowledge of the time periods when exports were restricted. In contrast, Ihle et al (2009) use a Markovswitching error correction model (MSECM) approach with an endogenous regime switch, similar to G€ otz et al (2013) and Djuric et al (2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The drivers of food prices have been variously reported as increased reliance on biofuels (Ajanovic 2011;Rosegrant 2008;Mitchell 2008), climate induced supply rigidities in some major agricultural countries (Baffes et al 2015;Fischer et al 1995;Rosenzweig and Parry 1994); and increasing demand pressure due to an expanding global population (Dyson 1996), among others. However, our understanding of the drivers of food prices especially in the developing world is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…A study of the Tanzanian maize market found that regional markets exert more influence on domestic prices than do global prices (Baffes, Kshirsagar and Mitchell 2015). While most countries are wheat and maize price-takers, the determination of international rice prices is less clear.…”
Section: International Price Transmissionmentioning
confidence: 99%